Synthesis, Structural Characterization, and Electrochemical Studies of New Oxovanadium(V) Complexes Derived from 2-Furanoylhydrazon Derivatives - Rahman Bikas; Hassan Hosseini-Monfared; Erwann Jeanneau; Behrouz Shaabani (Journal of Chemistry)
Five monooxovanadium(V) complexes [VO(L1)(OCH3)(OHCH3)] (1), [VO(L2)(OCH3)(OHCH3)] (2), [VO(L3)(OCH3)(OHCH3)] (3), [VO(L4)(OCH3)(OHCH3)] (4), and [VO(L5)(OCH3)(OHCH3)] (5) were synthesized and characterized by IR, NMR UV-Vis, and single-crystal structure analysis [H2L1=(E)-N′-((2-hydroxynaphthalen-1-yl)methylene)furan-2-carbohydrazide, H2L2=(E)-N′-(2-hydroxybenzylidene)furan-2-carbohydrazide, H2L3(E)-N′-(5-bromo-2-hydroxybenzylidene)furan-2-carbohydrazide, H2L4=(E)-N′-(2-hydroxy-5-nitrobenzylidene)furan-2-carbohydrazide, H2L5=(E)-N′-(2-hydroxy-5-iodobenzylidene)furan-2-carbohydrazide]. In all 1–3 structures the vanadium atom has a distorted octahedral coordination with the three meridional donor atoms from the Schiff base dianion (L1–3)2− and one methoxylato group occupying the sites of the equatorial plane. The oxo group and one methanol molecule occupy the apical sites. In the complexes 1, 2, and 3 the conformation of 2-furanyl oxygen atom relative to the carbohydrazide oxygen atom is s-anti, s-anti/s-syn, and s-syn at 293 K, respectively. Cyclic voltammetric experiments of the solution species 1–5 in DMSO revealed a quasi-reversible behavior.